The Art of Rhetoric (Institutiones Oratoriae, 1711-1741) : From the definitive Latin text and notes, Italian commentary and introduction by Giuliano Crifò. Translated and Edited by Giorgio A. Pinton and Arthur W. Shippee - Vico, Giambattista, (Value Inquiry Book Series ;, 1996)
Gustavo Costa reviewing the Italian edition of Vico's Institutiones Oratoriae in New Vico Studies 9 (1991), has written that Rhetoric is the mainspring of an important trend of Vichian studies which initiated at the beginning of the twentieth century and had its manifestation in John D. Schaeffer's Sensus Communis: Vico, Rhetoric, and the Limits of Relativism (Durham: Duke University Press, 1990), where Schaeffer aptly noted, summing up a long exegetic tradition, Vico was imbued with rhetoric and convinced of its centrality to Western civilization. Unfortunately, the editions of Vico's works published in English have not yet included the Institutiones Oratoriae , which more or less reflects the lectures on rhetoric given by Vico at the University of Naples, starting with the academic year 1699-1700 and going through 1739-1741. The manual on rhetoric was used in Italy up to the end of the nineteenth century and established the common curriculum in rhetoric to be followed in all Universities. This English edition offers a text of the Institutiones complete on the base of the four known extant manuscripts. It offers the marginal glosses made by Vico's students, a collection of Vico's phrases and explanations of terms collected by some of the students, a glossary of Latin words and rhetorical terms from the Latin text, and a wealth of information in the commentary. The Art of Rhetoric is the manual for everyone who wants to know what rhetoric is, how it was employed in the forum or the courts, how it could be learned from the classic orators, and how it can be used whenever we speak for convincing, praising or motivating.